Penerapan Akuntansi dalam Meningkatkan Akuntabilitas Keuangan UMKM pada Toko Bakso dan Mie Ayam Garuda - Clarissa Najwa Chaliza; Kennia Rismaratri; Muhammad Ismail; Nafisa Aulia Martsyah; Risna Wulandari Satria Negara (Universitas 45 Surabaya, 2026)
This research is motivated by the importance of implementing accounting for Micro, Small, and Medium Enterprises (MSMEs) in improving financial accountability and supporting more appropriate business decision-making. However, in practice, many MSMEs still maintain simple financial records that do not comply with applicable accounting principles. This condition has the potential to cause inaccurate financial information and make it difficult for business owners to evaluate their business performance. This study aims to analyze the role of accounting in improving financial accountability at the Garuda Meatball and Chicken Noodle Shop, identify the form of financial recording used, and identify the obstacles faced in implementing accounting in the business. The research method used is a descriptive qualitative approach with data collection techniques through in-depth interviews with the business owner and related parties. The results show that financial records are still done manually and simply, without adequate account separation according to accounting principles. Nevertheless, the business owner has implemented a separation between personal and business finances. The application of accounting, although still limited, has been proven to play a role in improving the accuracy of financial reporting, controlling operational costs, and the ability of business owners to evaluate the performance and financial condition of their business. This study concludes that implementing a simple accounting system, particularly a digital one, is essential for MSMEs to improve financial accountability and support future business sustainability.